PENGARUH HUMAN RELATION, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN RINTISAN (START UP) DSOCETY CABANG MEDAN - Prayogi, Mugi Anggara; Dirbawanto, Nana Dyki (Transpublika Publisher, 2023)
This study aims to determine how Human Relations, Work Discipline, and Work Environment affect Employee Performance at the Medan Branch of DSociety Start Up Company. This research employed quantitative research techniques. The population used in this research was employees of the DSociety Medan Branch Start Up Company, with a sample size of 31 respondents. Purposive sampling was used in this research. The data was collected using a questionnaire and a Likert rating. The classical assumption test, multiple linear regression analysis, multiple correlation analysis, and SPSS hypothesis testing were used in this research. According to the findings of this research, Human Relations, Work Discipline, and Work Environment all have an impact on Employee Effectiveness. Based on the findings of the determination test, it was discovered that the Adjusted R Square value of 0,375 or equals 37.5%, implying that there is a direct correlation between the variables of Human Relations, Work Discipline, and Work Environment, and Employee Performance. The R Square value of 0,375 (37,5%) on the independent variables Human Relations, Work Discipline, and Work Environment has a simultaneous impact of 37,5% on the dependent variable, namely Employee Performance, while the rest is affected by other variables not examined by this research.